Pengaruh Penggunaan Media Kahoot Terhadap Hasil Belajar Materi Keragaman Suku Bangsa dan Budaya pada Siswa Kelas IV UPT SD Negeri 232 Gresik - Wulandari, Diah Ayu; Suprihatien, Suprihatien; Yuanta, Friendha (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the influence of the use of Kahoot media on the learning outcomes of ethnic and cultural diversity materials. This study uses a quantitative approach with a type of quasi experiment research whose population is all grade IV students, which is divided into two groups, namely class IV A with 14 students as the experimental group and class IV B with 13 students as the control group. The data collection technique used is a test in the form of multiple-choice questions. Validity and reliability tests are carried out to test the instrument. Furthermore, a normality test was carried out with the results of the variable =2,26, the variable while , while the results of the postes homogeneity test this was stated that both variables were declared to be normally distributed and homogeneous. To find out whether or not there is an influence of Kahoot media in learning, the results of which showed that the learning outcomes of the Ethnic and Cultural Diversity material of grade IV A students who were taught using Kahoot learning media were better than without using Kahoot media in learning on Ethnic and Cultural Diversity material.